Of lion manes and human beards: some unusual effects of the interaction between aggression and sociality - Blanchard, D. Caroline (Frontiers in Behavioral Neuroscience, 2010)
Abstract The function of manes in lions has been a topic of scientific interest since Darwin (1871) suggested that it provides protection in intraspecific fights. Recent experimental studies on wild lions have emphasized the role of female selection, but analyses of specific attack behaviors and targets, and the social consequences of manelessness for lions living in very hot climates suggest that male manes may indeed mitigate the outcomes of intraspecific male attack and thus serve a permissive function for multimale + female groups, facilitating protection of prides against takeovers and infanticide by nomadic males. Humans also have unusual structural protections for the head, face and neck, areas that are especially accessible during intraspecies attack, and highly vulnerable to damage. One of these, the beard, consists of coarse hairs that grow indefinitely, but only for males, and only during and following puberty; suggesting that it, like the lion’s mane, may serve as protection in intraspecies male fights. Such structural protections may reflect a specific combination of lethal weaponry and social lifestyle, particularly when these are developed so rapidly that they are not accompanied by the evolution of complex attack-inhibiting social behaviors.